Integrating Art and Narrative to Enhance Quality of Life in Palliative Care - Jennifer Fortuna (Scholarworks @ WMU, 2018)
Lacie Lee Wallace, a mixed-media artist from Wheeling, West Virginia, is featured on the cover of the Fall 2018 issue of The Open Journal of Occupational Therapy (OJOT). The photograph depicts Lacie holding a selfportrait painted by artist CeCey Rose. Lacie's physical appearance in the photograph is strikingly different from the physical appearance of the woman featured in the painting. The portrait was created 4 years before Lacie was diagnosed with advanced stage colon cancer. In the year following the diagnosis, Lacie lost nearly 100 lbs. as a result of an aggressive treatment regimen. When the palliative care team at West Virginia University Ruby Memorial Hospital launched a clinical study on narrative medicine, Lacie was one of the first patients to participate. Throughout her illness experience, Lacie found comfort in sharing both her art and her life story. Lacie's personal narrative made it clear just how meaningful art was in her life. Narrative medicine empowered Lacie's palliative care team to improve patient care and enhance her quality of life.